Issue Information. (18th March 2020) - Gentile, Francesco; Elmenoufy, Ahmed H.; Ciniero, Gloria; Jay, David; Karimi‐Busheri, Feridoun; Barakat, Khaled H.; Weinfeld, Michael; West, Frederick G.; Tuszynski, Jack A.
Abstract : Cover artwork: The cover image is based on the Research Article Computer‐aided drug design of small molecule inhibitors of the ERCC1‐XPF protein–protein interaction by Francesco Gentile et al., https://doi.org/10.1111/cbdd.13660 .